The effect butadiene and acrylonitrile components on the relaxation properties of butadiene-akrylonitrile copolymers - Bartenev, Georgij; Shut, Nikolai; Baglyuk, Sergey; Tulinova, V. (My University, 1988)
The majority of relaxation transitions in poly (butadiene-co- acrylonitrile) that are observed above the glass transitions temperature are connected with the butadiene component. The acrylonitrile component affect the glass transitions temperature and temperature of chemical decomposition of the polymer, and it leads also to the occurrence of the relaxation process connected with the mobility of local dipole-dipole cross bonds.
Keywords: релаксаційні переходи; сополімери бутадієна і акрилонітрила; температура склування; температура хімічного розпаду; релаксационные переходы; сополимеры бутадиена и акрилонитрила; температура стеклования; температура химического распада; relaxation transitions; poly (butadiene-co-acrylonitrile); glass transitions temperature; temperature of chemical decompositions; кафедра фізики та професійної безпеки